Pengembangan Media Pembelajaran Kas Kecil Berbasis Web untuk kompetensi keahlian Manajemen Kantor dan Layanan Bisnis SMK solusi Digitalisasi bidang Perkantoran - Santoso, Tri Nugroho Budi; Ismanto, Bambang; Sambara Sitorus, Destri; Rina, Lelahester (Universitas Kristen Satya Wacana, 2024)
The world of business and industry (DUDI) is currently experiencing a significant transformation due to the influence of technology, this is characterized by machines replacing human labor or what is often known as the Industrial Revolution 4.0. Vocational High Schools (SMK) as providers of Human Resources who are ready to work have big challenges. Based on the results of observations made on the competence of Office Management and Business Services Vocational Schools in Salatiga, Boyolali and Surakarta, there is one subject in Automation and Financial Governance that still uses conventional calculations. Based on the above background, this research focuses on developing web-based petty cash learning media as a technological innovation to answer the needs of human resources who master technology. The research method used is R&D (Research and Development) which starts from the analysis, design, development, implementation and evaluation stages. The research results show that the web-based petty cash system is suitable for use. The Feasibility Test showed that information systems experts got a final score of 4.67, material and content experts got a final score of 4.35, and learning media experts got a final score of 4.67. So it can be said that in terms of system, material, content and learning media, the petty cash system as a learning media in vocational schools is